2002
DOI: 10.1080/00984100290071649
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Ultrafine Insoluble Iridium Particles From Lung Epithelium to Extrapulmonary Organs Is Size Dependent but Very Low

Abstract: Recently it was speculated that ultrafine particles may translocate from deposition sites in the lungs to systemic circulation. This could lead to accumulation and potentially adverse reactions in critical organs such as liver, heart, and even brain, consistent with the hypothesis that ultrafine insoluble particles may play a role in the onset of cardiovascular diseases, as growing evidence from epidemiological studies suggests. Ultrafine (192)Ir radio-labeled iridium particles (15 and 80 nm count median diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
503
1
11

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 854 publications
(533 citation statements)
references
References 14 publications
18
503
1
11
Order By: Relevance
“…Nanosized TiO 2 samples were prepared using several gas phase synthesis methods: a diffusion flame aerosol reactor (Jiang et al 2007), a premixed flame aerosol reactor (Thimsen and Biswas 2007), a furnace aerosol reactor (Namiki et al 2005;Okuyama et al 1986), and a spark aerosol reactor (Kreyling et al 2002). The diffusion flame aerosol reactor was used to synthesize TiO 2 nanoparticles with large size (≥ 30 nm) and different crystal structures (anatase; anatase and rutile mixtures).…”
Section: Nanoparticle Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanosized TiO 2 samples were prepared using several gas phase synthesis methods: a diffusion flame aerosol reactor (Jiang et al 2007), a premixed flame aerosol reactor (Thimsen and Biswas 2007), a furnace aerosol reactor (Namiki et al 2005;Okuyama et al 1986), and a spark aerosol reactor (Kreyling et al 2002). The diffusion flame aerosol reactor was used to synthesize TiO 2 nanoparticles with large size (≥ 30 nm) and different crystal structures (anatase; anatase and rutile mixtures).…”
Section: Nanoparticle Synthesis and Characterizationmentioning
confidence: 99%
“…The properties of TiO 2 nanoparticles were controlled by adjusting the reactant feed rates and the temperature-time history in these reactors. Amorphous TiO 2 nanoparticles with small sizes were produced using a spark aerosol generator as reported previously (Kreyling et al 2002). A titanium electrode was used and the spark was generated in an oxygen stream.…”
Section: Nanoparticle Synthesis and Characterizationmentioning
confidence: 99%
“…However, it is important to note that this lung toxicity database has been limited to studies of three types of nanoparticles: titanium dioxide, carbon black and diesel particles (Warheit, 2004). NPM may also translocate within the body, for example from the nose and lungs to the central nerve system, the brain, into the systemic circulation and to organs like the liver (Nemmar et al, 2001;Takenaka et al, 2001;Kreyling et al, 2002;Oberdorster et al, 2002;Takenaka et al, 2004). The research covering the new types of NPM is limited and the number of studies of the environmental impacts of NPM are few.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations provided evidence that the UFPs can be translocated from the lungs to the extrapulmonary organs (i.e., liver, heart, spleen, brain) via the blood circulation (Nemmar et al, 2001;Takenaka et al, 2001;Kreyling et al, 2002;Oberdörster et al, 2002). Indeed, Nemmar et al (2001Nemmar et al ( , 2002a have reported that intratracheally instilled UFPs in the form of ultrafine 99m Technetium-labelled carbon particles (100 nm) or albumin nanocolloid particles (diameter < 80 nm) are quickly translocated from the lung into the systemic circulation in hamsters and humans; radioactivity was detected in blood at 1 minute and 5 minutes, respectively.…”
Section: Introductionmentioning
confidence: 99%